Strategi Komunikasi Pemasaran PT KAI Daop 5 Purwokerto dalam Optimalisasi Jumlah Penumpang Kereta Api - Alip Akbar Naufal Rabbani; Desti Rahma Pertiwi; Iklima Hafidah Praja (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
This study analyzes the marketing communication tactics implemented by PT KAI Daop 5 Purwokerto to increase the number of train passengers, emphasizing advertising, direct marketing, online marketing, sales promotions, and public relations management. The method used in this study is qualitative with data collection techniques in the form of interviews, observations, and document collection. The findings of this study indicate that the communication approach used is integrated through traditional and digital media channels, where the use of social media and digital applications has proven effective in increasing customer participation and loyalty. In addition, promotional initiatives such as discounts and special fares are able to attract more passengers, especially during off-peak periods, while the public relations function helps in creating a good image and maintaining interaction with the community. Overall, the marketing communication tactics implemented are able to increase public awareness and the number of train users, although still facing challenges from competition from other transportation modes and changes in consumer habits.